Energy and exergy analysis of prosumers in hybrid energy grids. Issue 6 (18th August 2018) - Manrique Delgado, Benjamin; Cao, Sunliang; Hasan, Ala; Sirén, Kai
ABSTRACT: Surplus energy can be a recurrent phenomenon in zero-energy buildings (ZEBs) with onsite generation systems, usually resulting in the export of excess electricity. Yet, converting electricity into heat and exporting it could improve the overall energy balance. This study analyses the energy and exergy performance of a Finnish nearly zero-energy building (nZEB) as a heat and electricity prosumer, and proposes alternative energy topologies to improve energy and exergy levels, primary energy demand and CO2 emissions. The results show that increasing the installed capacity of the photovoltaic systems would lead to zero energy, exergy, emissions and a balance of primary energy. However, by instead using the surplus electricity to drive a heat pump and export heat, the currently installed capacity would lead to a net energy export of over 4000 kWh/a. Thus, energy conversion could significantly enhance the contribution from heat and electricity prosumers to smart energy grids, though not without affecting other criteria. Two management strategies arise: favouring heat export improves the net energy and CO2 emissions reduction but lessens the net exergy, while favouring electricity export improves the net exergy and primary energy reduction. The findings highlight that energy conversion can enhance nZEB performance and its exchange with hybrid grids.